80.3k views
5 votes
-3(2x-5)=-12x+15-18x

User Zardilior
by
6.2k points

2 Answers

4 votes

Answer:


-3(2x-5) = -12x +1 5 - 18x \\Combine like terms\\-3(2x-5) = -12x - 18x + 15\\Add similar elements\\-3(2x-5) = -30x +15\\Expand\\-6x+15-15 = -30x +15 -15\\simply\\24x = 0\\divid both sides by 24\\(24x)/(24) = (0)/(24)

x = 0

User Thomas Barnekow
by
6.2k points
1 vote

Answer:

x = -3

Explanation:

-3(2x+-5)= -12x+15+-18 Cange to addition

-6x+15=-12x+15+-18 Distribute

-6x+15 = -12x+-3 Combine like terms

(-6x+12x)+15=(-12x+12x)+-3 Add 12x to both sides

6x (15-15) = -3-15 Subtract 15 from both sides

6x/6 = -18/6 Divide both sides by 6

x = -3

User Mor Sagmon
by
6.5k points